PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM PERJANJIAN BAKU JUAL BELI PERUMAHAN DENGAN PIHAK PENGEMBANG DI BALI - Brahmanta, A.A Gde Agung; R, Ibrahim.; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016)DO - 10.24843/AC.2016.v01.i02.p08, 2016)
The rapid population growth makes the need for homes also increase. There are many emerging developer companies that offer home that could be obtained on credit. Real Estate Developer parties usually make an agreement with consumers in the form of standard contract, so that the consumers here have no bargaining power but to accept what is specified by the developer. This causes consumer to have less legal protection as opposed to what is contained in the provisions of Law No. 8 of 1999 concerning Consumer Protection. The problem faced is how the position of the buyers as consumers in the purchase of standard agreement of housing, as well as how the legal protection that can be provided to the consumer in the standard housing sale and purchase agreement with developers in Bali. This research is empirical legal research whose objects of study are the terms and provisions regarding the enforcement or implementation of normative law (codification, law or contract) is in action / in abstracto on any legal events that occur in the community (in concreto). The data source used in this study is primary data and secondary data. The results of this study indicate that the Status of the buyer as a consumer in the standard housing sale and purchase agreement has a weaker position compared to the business party (developer), this is because the purchase agreement offered by the business is made in the standard contract format so that consumers do not have bargaining power over what is contained in the clauses of the home purchase agreement. Legal protection that can be provided to the consumer in standard housing sale and purchase agreement with developers in Bali, namely if in the field there is a breach of the provisions set out in the Consumer Protection Act, a developer as the party carrying out the business can legally be sued by consumers as parties who feel aggrieved, then other measures are that a developer must also adjust the standard clause in the purchase and sale agreement that it offers is still at odds with this Law.
Keywords: protection, consumer, standard agreement, developer